The Effect of the Assignment to Make a Mind Map Before the Implementation of Discovery Learning on the Knowledge Competencies of Class VII SMPN 2 Lubuk Alung - Puput Putri; Helendra Helendra; Ganda Hijrah Selaras; Ardi Ardi (ATRIUM PENDIDIKAN BIOLOGI, 2020)
The research is based on the problems that exist in SMPN 2 Lubuk Alung, the students’ Cognitive competency are still low. One of the efforts that is done to increase students’ Cognitive competency is to apply  the assigment to make a mind map before is applied the discovery learning on students VII grade learning competencies at SMPN 2 Lubuk Alung. This research  used a randomized control group-only design. The population is all student of class VII SMPN 2 Lubuk Alung registered in 2018/2019. Sampel was taken by using purposive sampling  technique and getting VII.1 as the eksperimen class, VII.2 as the control class. The hypothesis was tested using the t-test, can be concluded that the competence of learners knowledge tcount2,52>ttabel1,67. This shows that the hypothesis is accepted. it can be concluded that the assignment create a mind map before applying the discovery learning gives positive effect on students knowledge competencies the VII grade at SMPN 2 Lubuk Alung Keywords: Mind Map, Discovery Learning, Cognitive Competency